Priming against environmental challenges and proteomics in plants: Update and agricultural perspectives - Tanou, Georgia; Fotopoulos, Vasileios; Molassiotis, Athanassios (Frontiers in Plant Science, 2012)
Priming is the cellular state in which the harmful effects of abiotic stress factors in plants are hindered by pre-exposure to a stimulus, thus resulting in greater survival. It is becoming increasingly evident that priming techniques (e.g. external application of natural or synthetic compounds in plants) can enhance the tolerance of crops to environmental stresses. Innovative systems biology approaches such as proteomics are currently recognized as essential tools to understand the molecular mechanisms underlying plant responses to environmental stimuli and priming phenomena. The few published proteomic studies on priming in the context of environmental stress identify key protein targets and signaling pathways which are being involved in the alleviation of negative effects of stress factors. Since priming is a very promising strategy in modern crop production management, further research is needed in order to establish the global picture of priming phenomena against environmental challenges as well as to characterize specific priming-related protein indicators in plants.